Premalignant and malignant lesions of the esophagus: a single institutional experience (2020)
Background: Esophageal malignancy is a highly aggressive tumor with a poor prognosis. A number of lesions occurring in the esophagus are associated with a high risk of malignant transformation. While the patterns of esophageal cancers have been documented in a number of African countries, there is a limited data on the Nigerian situation. This study was aimed at reviewing the histological patterns of premalignant and malignant lesions of the esophagus. Methods: This was a 10 year retrospective study of histologically confirmed premalignant and malignant lesions of the esophagus seen at the University College Hospital, Ibadan, between January 2009 and December 2018. Data retrieved from the departmental records were analyzed using the SPSS computer software version 20.0. Results: There were 45 cases diagnosed with premalignant lesions and 32 cases diagnosed with malignant lesions out of the 363 biopsies during the study period. The most common premalignant lesion was Barret’s esophagus (68.9%). Premalignant lesions were more common in males (64.4%). The mean age for patients with a diagnosis of premalignant lesions was 55 years. The mean age at the diagnosis for esophageal cancer was 61.5 years. Squamous cell carcinoma was the predominant histological subtype seen (65.6%) with adenocarcinomas accounting for the remainder of cases (35.4%). Conclusion: Squamous cell carcinoma is the most common malignancy of the esophagus in our study. Adenocarcinomas of the esophagus were not as rare as documented in previous African studies. This finding may imply a changing pattern in esophageal malignancies in tandem with the pattern in Western countries.